ABC Costing: Management Accounting Through the Dairy Livestock SME in Colombia - Ruiz-Torres, Juan; Fonseca-Cifuentes, Gina; Fandiño Núñez, Johan (Journal of the University of Zulia, 2024)
The article has developed the ABC costing system, as an approach to the small dairy farming SME in Colombia. The methodology includes conceptual elements developed by Cuervo Tafur, Osorio Agudelo and Duque Roldán (2013); Bruggeman et al. (2005); Hicks (1998); Kaplan and Cooper (1998) and Sánchez-Mayorga & Millán-Solarte (2010) with the definition of six general phases that define the cost system in question. In this way, the results allow the involvement of basic and support activities (Porter, 1995) grouped into cost centers, for the identification of the costs of the product and the biological asset in accordance with IAS 41. It has been concluded that this The accounting mechanism allows the definition of strategic cost management based on the value-generating elements and the possibility of optimal tools related to business profitability.